Pengaruh Pelaksanaan Kurikulum K-13 Terhadap Peningkatan Mutu Pendidikan SMK Darussalam Blokagung Tahun Pembelajaran 2018/2019 - Al Rosid, Moh. Harun; Hasanah, Riyan Uswatun (Jurnal Manajemen Pendidikan Islam Darussalam, 2019)
The purpose of this study is 1). to find out the implementation of the K-13 curriculum at SMK Darussalam Banyuwangi, 2) to find out the quality of education at SMK Darussalam Blokagung Banyuwangi; 3). to determine the effect of the implementation of the curriculum (K-13) on the quality of education in SMK Darussalam, Banyuwangi Blockagung. This type of research is quantitative descriptive using observations, questionnaires, and documentation for data collection techniques while the analysis uses simple linear regression. The population of this research is the teaching staff and educational staff of SMK Darussalam with 71 respondents as the actual sample. After analyzing that the results were found that the implementation of Curriculum K-13 (X) is very influential on the Education Quality of SMK Darussalam as evidenced by the results of data analysis of 60.2% while the remaining 39.8% by other variables.